The Development of Consonant Reading Skills by Using Educational Games Activities of Kindergarten 2 Students - สุวรรณสัมฤทธิ์, ชลาภรณ์; ศรีบุญรอด, ชุติณัชชา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of research were 1) to develop of consonant reading skills and 2) to compare consonant reading skills of kindergarten 2 students by using educational games activities. The sample of the research were 3 students in kindergarten 2, Thammasirisuksa Nonthaburi school who study in academic year 2026 using purposive sampling. The research instruments used in this research were the activity lesson plans of educational game which had quality at the high level and the consonant reading skills assessment form which had Index of Item objective congruence equal 1. 00 for all items. The statistics for analysis the data were mean and percentage.            The results found that: 1) the kindergarten 2 students had the consonant reading skills after using educational games at good level and 2) after engaging with the education games students had higher consonant reading skills than before the activity delivery.